1980
DOI: 10.1136/thx.35.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lobectomy on lung function.

Abstract: The effect of lobectomy on lung function was investigated in 16 patients in whom comprehensive lung function tests were performed before and between six weeks and six months after lobectomy. The operation was well tolerated even by patients with quite severe airways obstruction. The effect of lobectomy on forced flow rates was in keeping with the change in lung volumes. There was no alteration in the distribution of ventilation and the diffusion capacity remained unchanged. The changes in the pressure volume c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 14 publications
1
20
1
2
Order By: Relevance
“…The answer depends mainly on the extent of resection. Various studies have looked at the functional loss after lung resection in terms of pulmonary function [16,44,113,[115][116][117][145][146][147]. ALI et al [115] and LODDENKEMPER et al [16] have shown that resections involving not more than one lobe lead to an early loss in pulmonary function with later recovery and little permanent deficit.…”
Section: Effect Of Lung Resection On Postoperative Pulmonary Functionmentioning
confidence: 99%
“…The answer depends mainly on the extent of resection. Various studies have looked at the functional loss after lung resection in terms of pulmonary function [16,44,113,[115][116][117][145][146][147]. ALI et al [115] and LODDENKEMPER et al [16] have shown that resections involving not more than one lobe lead to an early loss in pulmonary function with later recovery and little permanent deficit.…”
Section: Effect Of Lung Resection On Postoperative Pulmonary Functionmentioning
confidence: 99%
“…Various studies have investigated the functional loss after lung resection in terms of pulmonary function tests (PFT) [2][3][4][5][6][7][8][9][10]. It is generally accepted that resections involving not more than one lobe lead to an early loss in PFT with later recovery and little permanent deficit, whereas pneumonectomies cause a bigger permanent functional loss [7,10].…”
mentioning
confidence: 99%
“…As the reduction in TLC puts the inspiratory muscles at a mechanical advantage, the absence of increase in PL,st,TLC would imply either a decreased inspiratory muscle strength, or a decreased chest wall compliance after LVRS. Similarly, the shift rightwards and downwards of the P-V curve also reported after LVRS, with volume expressed in absolute terms [66,71] or in per cent predicted TLC [67], is a usual feature after lung resection [73]. This shift would be more relevant if it was shown to occur with volume expressed as a percentage of actual TLC.…”
Section: Static Mechanics Of the Respiratory Systemmentioning
confidence: 98%